Evaluation of the radiation risk of medical examinations in the Russian Federation taking into account the age and sex distribution of the patients - V. Yu. Golikov (Радиационная гигиена)
The aim of the study was to develop a methodology that allows taking into account the age and sex dependencies of the risk of radiogenic cancer and the age and sex distribution of the patients to evaluate the collective risk due to separate X-ray examinations and medical exposure in the Russian Federation as a whole. Methodology is based on the use of lifetime risk coefficients estimated for the Russian and Composite population and the results of the study of typical doses of patients for various X-ray examinations in the Russian Federation. It is shown that the assessment of the radiation risk of separate X-ray examinations calculated using lifetime age and sex risk coefficients, organ doses and age distributions of patients may differ up to order of magnitude from the risk assessment based on effective dose and nominal risk coefficients. The difference in estimating of the collective risk of total medical exposure in the Russian Federation by these two methods reached 2.5 times in 2018.